2017
DOI: 10.1097/dss.0000000000001161
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Actinic Keratoses: A Randomized Split-Site Approach Comparison of Sequential 5-Fluorouracil and 5-Aminolevulinic Acid Photodynamic Therapy to 5-Aminolevulinic Acid Photodynamic Monotherapy

Abstract: Sequential therapy with 5-FU-ALA-PDT is more effective at AK clearance at 6 and 12 months compared to ALA-PDT monotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
1
10
0
3
Order By: Relevance
“…Importantly, normal non-irradiated skin showed no difference in intracellular PpIX with either sequential 5-FU plus 5-ALA or when given 5-ALA alone compared to skin cells exposed to neither [46]. Human clinical use in using sequential topical 5-FU, followed by 5-ALA PDT compared with 5-ALA PDT alone in treating actinic keratoses indicate that pretreatment with 5-FU increases 5-ALA PDT effectiveness [47,48].…”
Section: The Drugmentioning
confidence: 99%
“…Importantly, normal non-irradiated skin showed no difference in intracellular PpIX with either sequential 5-FU plus 5-ALA or when given 5-ALA alone compared to skin cells exposed to neither [46]. Human clinical use in using sequential topical 5-FU, followed by 5-ALA PDT compared with 5-ALA PDT alone in treating actinic keratoses indicate that pretreatment with 5-FU increases 5-ALA PDT effectiveness [47,48].…”
Section: The Drugmentioning
confidence: 99%
“…Although the therapeutic advantage of combining 5FU with ALA-PDT for treating AKs has been reported by several other groups (57)(58)(59)(60)(61)(62), our studies as summarized above provided knowledge about the underlying mechanisms of action when 5FU and ALA-PDT are combined. Thus, we showed that cPDT involving 5FU pretreatment successfully improved the therapeutic response of PDT in preclinical and clinical studies involving SCCs and AKs, and that a central mechanism is induction of differentiation by 5FU which enhances the levels of PpIX accumulation by upregulating heme biosynthetic enzymes, eventually resulting in increased phototoxicity and better lesion clearance (8,48).…”
Section: Fu In Combination With Photodynamic Therapymentioning
confidence: 81%
“…ALA‐PDT and 5FU, when applied separately, have given similar clearance response in several clinical trials (54–56). A few studies using a combination of 5FU as a pre‐ or post‐PDT treatment have reported a better lesion clearance rate when 5FU was applied prior to PDT (57–60). Following these reports and to extend our preclinical findings (described above) into the clinical arena, a clinical trial in patients with widespread AK lesions of the face or scalp (a disease for which topical 5FU is FDA‐approved) was undertaken (48).…”
Section: Introductionmentioning
confidence: 99%
“…40 ALA-PDT with pre-treatment with 5-FU cream twice daily for 7 days showed increased AK clearance rates of 100% versus 82.6% ( P = .0002) at 12 months compared to ALA-PDT alone. 41 A meta-analysis of 10 RCTs with a total of 277 participants found that the combination of PDT with topical treatments including imiquimod, 5-FU, ingenol mebutate, tazarotene, and calcipotriol increased complete clearance rates (RR: 1.63; 95% CI: 1.15-2.33) compared to PDT alone. 42 The evidence suggests that daylight-PDT is first-line for the treatment of grade I to II AKs and that conventional PDT is first-line for managing grade III AKs, but more work is required to clarify the role of combination PDT treatments with micro-needling and lasers in AK management.…”
Section: Currently Approved Indicationsmentioning
confidence: 99%